PENERAPAN MOEDEL PEMBELAJARAN TUTOR TEMAN SEBAYA DALAM KELOMPOK KECIL PADA STANDAR KOMPETENSI MEMPERBAIKI SISTEM PELISTRIKAN KELAS XI TSM 3 - Angga Lesmana Hadi, - (2009)
This research in background overshadows by study applying claiming student liveliness, while learning only as fasilitator to assist student in process of study. Usage of study model executed felt indigent to increase student activity in learning, so that study is more in domination by teacher. Piaget arises that knowledge is not obtained quiescently by someone. According to konstruktivisme opinion sight, learning is consider as optimal as possibly involvement process of student, study is not knowledge transmission, but entangling arrangement of situation of class. Based on above understanding, perceivable that theoretical learnt konstruktivisme, irremovable knowledge off hand from mind learns to student mind. Learned only functioning as mediator, fasilitator, and friend making situation kondusif for the happening of construction of knowledge at student. On the basis of reality this is, hence teacher must be able to do arrangement of condition of situation of class causing can happened study process done actively by student, by doing innovation and approach, good of that is in usage of media and or method forwarding of causing study process can take place active. This research aim to get information about how big applying of study model of friend tutor coeval in small group at elementary interest improve repairs electricity system can increase activity and result of class student learning XI TSM 3 in SMK Negeri 8 Bandung. Method applied at this research is Penelitian Tindakan Kelas (PTK) performed within frame breaks problems by trying to applies study strategy to overcome problems happened relating to process and result of student learning which unmatched to hope. Research subject in this PTK is all class student XI TSM 3 SMK NEGERI 8 Bandung school year 2009/2010. Research applied is know how big student learning activity and result of student learning by using study model of friend tutor coeval in small group. Data in this research obtained by using observation sheet and evaluation test sheet pre-test and post-tes. Based on observation in three cycles, got average of student activity in three cycles equal to 74,02% stays at good category. While result of learning student by using evaluation pre-test and post-test, got: 1) Average value for third of its the cycle 7,27 complete with medium category, has fulfilled KKM. 2) Average of complete percentage learnt at last cycle equal to 91,18%. All student experiences improvement result of minimum learning categorizes is medium according to normalization criterion Gain. Based on the result, inferential that study model of friend tutor coeval can increase activity and result of class student learning XI TSM 3 in SMK Negeri 8 Bandung